Evaluation Of The Radiological Situation In Algeria After The Algeciras Incident - NOUREDDINE, A.; HAMMADI, A.; BOUDJENOUN, R.; MENACER, M.; ALLALOU, A.; BENKRID, M.; MAACHE, M. (Mediterranean Marine Science, 2003)
The present study has been carried out in the framework of our environmental monitoring programme and immediately after being informed by the IAEA of possible accidental releases of 137 Cs into the air, which might have been released between May 25 th and the first of June 1998 from the Acerinox factory in Algeciras (Spain). Algericas is the region where a steel-processing factory has been set up. During the work procedure, a radioactive source of 137 Cs passed through the furnace resulting in accidental releases into the atmosphere. This radioactive contamination was detected in France, Switzerland, Italy and Germany, and some radioactivity measurements were carried out by the Commissariat A l’Energie Atomique to evaluate the gamma radiation status in areas selected in Algeria. The approach adopted in our case was to start in situ gamma-radiation measurements and to collect air and soil samples as well from a selected area in Algiers. Afterwards, and in order to have more reliable results, a sampling program was carried out in July 1998, in the frame of which some sampling stations were established in the west of Algeria, based upon Algerian meteorological data during the period of incident. A total number of 16 environmental samples from 9 stations, namely, soil, sediment, vegetation and seawater were collected, followed by in situ gamma radiation measurements in each sampling location. Soil, sediment and vegetation samples were analysed by direct gamma spectrometry, whereas, sea water samples were analysed radiochemically using microcrystalline AMP for coprecipitation and gamma counted. Taking into consideration the background levels of radioactivity in the studied areas, obtained by our previous monitoring programs, the results obtained do not show any increase of 137 Cs resulting from the incinerated Caesium source in the Acerinox steel factory in Algeciras, Spain. The conclusion drawn by this work is that the investigated area was not affected by the release of 137 Cs.